Pulmonary Embolism: Contemporary Medical Management and Future Perspectives - Barco, Stefano; Konstantinides, Stavros V. (Annals of Vascular Diseases, 2018)
Pulmonary embolism (PE) contributes substantially to the global disease burden. A key determinant of early adverse outcomes is the presence (and severity) of right ventricular dysfunction. Consequently, risk-adapted management strategies continue to evolve, tailoring acute treatment to the patients’ clinical presentation, hemodynamic status, imaging and biochemical markers, and comorbidity. For subjects with hemodynamic instability or ‘high-risk’ PE, immediate systemic reperfusion treatment with intravenous thrombolysis is indicated; emerging approaches such as catheter-directed pharmacomechanical reperfusion might help to minimize the bleeding risk. Currently, direct, non-vitamin K-dependent oral anticoagulants are the mainstay of treatment for acute PE. They have been shown to simplify initial and extended anticoagulation regimens while reducing the bleeding risk compared to vitamin K antagonists. (This is a review article based on the invited lecture of the 37th Annual Meeting of Japanese Society of Phlebology.)